Study of the Effect of Asana-Pranayama and Sangha Exercises on the Vital Capacity of Obese Students - Gidiyan J. Baraiya,; Dr. Devangkumar R. Patel, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The purpose of this research study was to study the effect of Asana-Pranayama and Sangha Vyavan activities on the vital capacity of obese students. This research study was limited to North Gujarat. In this research study, a total of 150 students from Sabarkantha district of North Gujarat were randomly selected as subjects. In this research study, students in the age group of 18 to 25 years were selected. In this research study, the subjects were divided into three groups. Group-A Asana-Pranayama group 50 students, Group-B Sangha Vyavan 50 students and Group-C Control group 50 students were selected, a total of 150 students were selected. For this research study, only obese students were selected as subjects. In the measurement standard, vital energy was measured using a picoflowmeter. To find out the effects of asana-pranayama and Sangha Vyavan activities on obese students, one-way analysis of covariance test was applied and the differences between the means were tested for significance at the 0.05 level using the Least Significant Difference Post Hock test. The conclusion was as follows. A significant improvement was observed in the vital capacity of the subjects selected from the 12-week asana-pranayama training and Sangha Vyavan training program of the method.